2013
DOI: 10.1017/s1368980013001894
|View full text |Cite
|
Sign up to set email alerts
|

Food choice, plate waste and nutrient intake of elementary- and middle-school students participating in the US National School Lunch Program

Abstract: Objective: To (i) evaluate food choices and consumption patterns of elementaryand middle-school students who participate in the National School Lunch Program (NSLP) and (ii) compare students' average nutrient intake from lunch with NSLP standards. Design: Plate waste from elementary-and middle-school students' lunch trays was measured in autumn 2010 using a previously validated digital photography method. Percentage waste was estimated to the nearest 10 % for the entrée, canned fruit, fresh fruit, vegetable, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
125
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(144 citation statements)
references
References 22 publications
14
125
2
3
Order By: Relevance
“…Other recent reports have also used digital photography to assess food intake in cafeteria or free-living settings and have found it to be a reliable estimation. [32][33][34] None of those studies have evaluated the relationship of FV to total energy, although one reported 43% average waste of fruit and 31% waste of vegetables among middle school students, and 37% and 34% (respectively) among elementary students, with total energy consumed lower than recommendations by the Child Nutrition and WIC Reauthorization Act of 2004. 33 For comparison, third through fifth graders in this study, currently participating in an F2S program, wasted an average of 26% of fruit and 27% of vegetable by volume (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Other recent reports have also used digital photography to assess food intake in cafeteria or free-living settings and have found it to be a reliable estimation. [32][33][34] None of those studies have evaluated the relationship of FV to total energy, although one reported 43% average waste of fruit and 31% waste of vegetables among middle school students, and 37% and 34% (respectively) among elementary students, with total energy consumed lower than recommendations by the Child Nutrition and WIC Reauthorization Act of 2004. 33 For comparison, third through fifth graders in this study, currently participating in an F2S program, wasted an average of 26% of fruit and 27% of vegetable by volume (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have reported high plate waste values at school canteens (6)(7)(8)(9) . In Portugal, studies developed in this setting found waste values higher than 30 % (10,11) and significantly higher than the acceptable limit of 10 % (12) .…”
mentioning
confidence: 99%
“…Previous research suggests that food waste in US public schools is substantial in magnitude and value (8,16,17) . The NSLP has been the subject of the majority of related studies (16,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) .…”
mentioning
confidence: 99%